Weight training by design : - Greenwald, Dale (McGraw-Hill, 2006)
Maximize workouts with the groundbreaking BAM Superset System No fads, no gimmicks, no false promises, Weight Training by Design gives students a sound, easy-to-follow, fully customizable program to help them take their workouts to the next level. The all-new BAM (Balanced Antagonistic Muscle) Superset is not your traditional superset. Flexible, dynamic, and totally customizable, BAM helps students accomplish greater gains at their own pace and level. Developed by experienced trainers, the BAM Superset combines exercises for opposing muscle groups. This speeds up students' workouts, reduces soreness and injury risk, and helps them build muscle mass in no time.